Menelisik Indeks Kepuasan Publik terhadap Program Tanggung Jawab Sosial dan Lingkungan (TJSL) di PT Pertamina Patra Niaga Integrated Terminal Panjang - Syarief, Ayu Nirmala Lutfie; Prasetyo, Catur Yogi; Pamungkas, Bayu Aji; Putri, Rinda Aryani (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2025)
This study aims to measure the public satisfaction index regarding the Corporate Social and Environmental Responsibility (CSER) activities of PT Pertamina Patra Niaga Integrated Terminal Panjang and to identify the categories of satisfaction indicators. The research was conducted on the ecobrick group in Kampung Baru Tiga, North Panjang Village, Bandar Lampung City, Lampung Province, involving a total of 30 respondents. The research variables were derived from the basic elements of public satisfaction index measurement as stipulated in the Regulation of the Minister of Administrative and Bureaucratic Reform No. 14 of 2017. The variables include knowledge of the company’s CSER program, program suitability with regional conditions, infrastructure and facility readiness, product quality, costs and tariffs, alignment with community needs, community satisfaction with services, community involvement, potential for business sustainability, human resources in business development, and program development innovation. The results indicate that the public satisfaction index for the CSR program of PT Pertamina Patra Niaga Integrated Terminal Panjang is 87.3, with all indicator values falling within the ‘good’ category.